The Extent of the Continuity and Protection of the Public Entity during Coronavirus Pandemic in Light of the Provisions of the Jordanian Legislation and Judiciary - Al-Andali, Mohammad Moqbel Salem (Journal of Economic, Administrative and Legal Sciences, 2021)
The administrative activity has two main aspects, namely: the administrative control and public entities management. As a consequence, it is responsible for the well-functioning of these entities and for maintaining the public system and its four elements, so it was granted by the legislator certain powers whether in normal or exceptional circumstances, and its works were put under control during all those circumstances however this control is the least possible on some of the pillars of the administrative decision during exceptional circumstances compared to normal circumstances in order to face the emergency through which the country is going, for example, the current exceptional circumstance due to Coronavirus outbreak, so the public administration, during the exceptional circumstances, may carry out from the administrative control authorities what it cannot carry out during the normal circumstances. However, that does not mean it is behaving without any restriction or control, rather it is subject to many restrictions and controls that the administrative jurisdiction is trying to ensure the commitment to it, so the administration will not take advantage of the exceptional circumstance to overthrow the public freedoms of individuals. The administration, even with the emergence of the exceptional circumstances, acts within the framework of the principle of legality and according to its rules, but it is legitimate of a special kind or exceptional one, which the administrative jurisprudence calls the term legitimacy of crises. Public entities are of a great importance in the life of the community, as they are created to satisfy the public needs that the state considers its duty to satisfy them regularly and without interruption, regardless of the difficulties and costs.
Keywords: public bodies; administrative decision; public office